2023
DOI: 10.1186/s12889-023-15440-1
|View full text |Cite
|
Sign up to set email alerts
|

Life in a time of COVID: retrospective examination of the association between physical activity and mental well-being in western Australians during and after lockdown

Abstract: Background The aim of this study was to examine physical activity and sedentary behaviours during Western Australia’s COVID-19 lockdown and their association with mental well-being. Methods Participants completed activity related questions approximately two months after a three-month lockdown (which formed part of a larger cross-sectional study from August to October 2020) as part of a 25-minute questionnaire adapted from the Western Australia Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(61 reference statements)
2
4
0
Order By: Relevance
“…Since the LTA can identify subpopulations based on the behavioral profiles, it can be useful for informing diverse targeted strategies to effectively plan future health promotion campaigns and procedures in future. For example, some of the topics that were identified in the studies by Bhoyroo et al (8) and Piggott et al (24) also emerged in the present study as being associated with specific subgroups. For instance, Piggott et al (24) reported that some people were "challenged to stay motivated and to find new ways to exercise in general or lacked motivation overall, " which is most likely be associated with inactive groups from the present study.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Since the LTA can identify subpopulations based on the behavioral profiles, it can be useful for informing diverse targeted strategies to effectively plan future health promotion campaigns and procedures in future. For example, some of the topics that were identified in the studies by Bhoyroo et al (8) and Piggott et al (24) also emerged in the present study as being associated with specific subgroups. For instance, Piggott et al (24) reported that some people were "challenged to stay motivated and to find new ways to exercise in general or lacked motivation overall, " which is most likely be associated with inactive groups from the present study.…”
Section: Discussionsupporting
confidence: 69%
“…For example, some of the topics that were identified in the studies by Bhoyroo et al (8) and Piggott et al (24) also emerged in the present study as being associated with specific subgroups. For instance, Piggott et al (24) reported that some people were "challenged to stay motivated and to find new ways to exercise in general or lacked motivation overall, " which is most likely be associated with inactive groups from the present study. Similarly, the present study revealed detailed information of the different characteristics of individuals that reported "no change" in Bhoyroo et al ( 8) study-that is, individuals who "remain" in their group in present study.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations